THE PRIMITIVE MATRIX COMPONENTS OF THE UNIQUE CARBONACEOUS CHONDRITE ACFER 094: A TEM STUDY - Greshake A. (My University, 1997)
The mineralogical and chemical characteristics of the fine-grained matrix (=<3 μm) of the unique primitive carbonaceous chondrite acfer 094 have been investigated in detail by scanning electron microscopy (sem) and analytical transmission (atem). generally, fine-grained matrix represents a highly unequilibrated assemblage an amorphous material, small forsteritic olivines (200-300 nm), low ca-pyroxenes (300-400 fe,ni-sulfides (100-300 nm). is basically unaffected secondary processes. only minor amounts serpentine ferrihydrite, as products hydrous alteration, are present. texturally, material acts groundmass to olivines, pyroxenes, sulfides, mostly exhibiting rounded or elongated morphologies. very few clastic mineral grains found. texture chemical composition consistent with origin disequilibrium condensation either cooling solar nebula circumstellar environment. such, may be considered possible precursor materials other types chondrites. non-classic (fo98-99) and pyroxenes (En97-100) are suggested to have formed either by condensation in the solar nebula under highly oxidizing conditions or by recrystallization from the amorphous material. The formation of these grains by fragmentation of chondrule components is unlikely due to chemical and microstructural reasons. Rapid cooling caused the observed intergrowths of clino/orthoenstatite in the Mg-rich matrix pyroxenes. Although some similarities exist comparing the fine-grained matrix of Acfer 094 with the matrices of the unequilibrated CO3 chondrite ALHA77307 and the unique type 3 chondrite Kakangari, Acfer 094 remains unique. Since it contains the highest measured concentrations of circumstellar SiC and the second highest of diamond (highest is Orgueil), it seems reasonable to suggested that at least parts of the amorphous material in the fine-grained matrix may be of circumstellar origin.